2018
DOI: 10.1021/acschembio.8b00558
|View full text |Cite
|
Sign up to set email alerts
|

A Guanidine-Based Synthetic Compound Suppresses Angiogenesis via Inhibition of Acid Ceramidase

Abstract: Angiogenesis generates new blood vessels from pre-existing vessels. Tumors induce the formation of new blood vessels to ensure sufficient oxygen and nutrients for their growth. Normally, angiogenesis is induced by various pro-angiogenesis factors, including vascular endothelial growth factor (VEGF). Inhibition of VEGF is a promising approach to cancer treatment. A guanidine-based synthetic compound, E2, was identified as a potent hit from 68 guanidine-based derivatives by screening for angiogenesis inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…From phage display biopanning, the E2 binding protein acid ceramidase 1 (ASAH1) was identified. The DARTS assay revealed that E2 increased the stability of ASAH1 against proteolysis with pronase . The binding of E2 to ASAH1 leads to suppression of vascular endothelial growth factor through the Akt signaling pathway, thus leading to inhibition of angiogenesis.…”
Section: Combination Of Darts With Lc‐ms/msmentioning
confidence: 99%
See 1 more Smart Citation
“…From phage display biopanning, the E2 binding protein acid ceramidase 1 (ASAH1) was identified. The DARTS assay revealed that E2 increased the stability of ASAH1 against proteolysis with pronase . The binding of E2 to ASAH1 leads to suppression of vascular endothelial growth factor through the Akt signaling pathway, thus leading to inhibition of angiogenesis.…”
Section: Combination Of Darts With Lc‐ms/msmentioning
confidence: 99%
“…DARTS assays of unmodified drugs can be combined with immunoblotting to validate the DARTS and LC‐MS/MS results and investigate the biophysical interactions of bioactive small molecules with target proteins . Alteration in the stability of the target protein by a bioactive small molecule after treatment with pronase indicates that there was a direct biophysical interaction between the two molecules.…”
Section: Biophysical and Biological Relevance‐based Target Validationmentioning
confidence: 99%
“…It should be noted in conclusion, that chemists continue to use thiourea oxides in the synthesis of guanidine-based pharmaceuticals. Thus, in 2019 Cho and coworkers have received guanidine-based compound which suppresses angiogenesis in human umbilical vein ebdothelial cells [26]. In the intermediate steps of the synthesis of this compound they used thiourea trioxide.…”
Section: Discussionmentioning
confidence: 99%
“…ACDase also regulates cancer cell motility through the activation of the ITGαVβ5/FAK signaling cascade [ 63 ]. Additionally, the significant roles of ACDase in angiogenesis, chronic inflammation, and tumorigenesis may contribute to cancer development and progression [ 66 , 67 ]. ACDase affects multiple factors in cancer pathogenicity, which adds to the complexity of the enzyme in the diagnosis and treatment of the disease.…”
Section: Role Of Ceramidase Activity In Human Non-heritable Diseasmentioning
confidence: 99%